Utrata złudzeń edukacji publicznej. Fatalne dziedzictwo, eskapizm elit, iskry nadziei - Kwieciński, Zbigniew (Studia Edukacyjne, 2018)
The article raises the question of the causes of the public education crisis, both the crisis in recent past and that conditioned by several centuries of Poland’s past. The position of Adam Podgórecki on the subject of comprehensive analyses of Polish society is particularly important. It combines two positions. He believes that Polish systemic crises can be put down to the experiences of post-totalitarianism and Polish unique defects persisting for several centuries. The author of the article negatively assesses the possibility of overcoming the crisis of public education by academic elites, which are responsible for the collapse of universities and the crisis of higher education. Common beliefs about public education have turned out to be illusions. The author sees the hopes of improving the state of public education in resistance to the destruction of democracy and to the strong ideological and political pressure. Openness to Europe and the world, which Poles do not give away, inspires hope, too.